If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(a + -5) = 26 Reorder the terms: 6(-5 + a) = 26 (-5 * 6 + a * 6) = 26 (-30 + 6a) = 26 Solving -30 + 6a = 26 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '30' to each side of the equation. -30 + 30 + 6a = 26 + 30 Combine like terms: -30 + 30 = 0 0 + 6a = 26 + 30 6a = 26 + 30 Combine like terms: 26 + 30 = 56 6a = 56 Divide each side by '6'. a = 9.333333333 Simplifying a = 9.333333333
| 25(x-11)= | | 2cos^2+cos+1=0 | | r-2.3=7.9 | | l=iPN | | (11-2)180= | | N+14=77 | | 4(11x-49)=4-2(x+5) | | 89=c+44 | | b+13=56 | | x+x*0.48=785.83 | | 13n=117 | | m-76=158 | | 7.9+x=12.3 | | 4x(x-3)+2x-x^2=3x^2+40 | | X=17-13 | | x^3-2x=-x | | x+8.9=9.7 | | 8x-8=-11 | | X=25-15 | | 8c-(3c+2)= | | 10x+7-4x=-8x-30+x | | 21=x-43 | | 2(2x+2)=-(2x+2) | | x+x*0.5=200 | | 0.5x+23=-15 | | xc-d=0 | | X/7=-1/2 | | 4x-10=98 | | 3(3x-1)+5=6(X+2) | | F(x)=2x-16x+31 | | 3x^2-7x-21=-1 | | 4(x-2)=5x+17 |